All-fiberized Mode-Locked Laser at 1.95 μm using copper chalcogenide cu2Te-based evanescent field - Ahmad, Harith; Aidit, Siti Nabila; Yusoff, Norazriena; Ismail, Mohammad Faisal; Ismail, N. N.; Abdul Kadir@Jaafar, Muhammad Zamzuri; Thambiratnam, Kavintheran (Elsevier Ltd, 2020)
For the first time, a copper telluride (Cu2Te) based saturable absorber (SA) was demonstrated for mode-locking in a thulium-doped fiber laser. Layers of Cu2Te were deposited onto a side polished fiber (SPF) using the optical deposition technique, forming an all-fiber SA device. The nonlinear optical properties of the SA device were investigated based on the balanced twin-detector measurement scheme. The Cu2Te-deposited (SPF) was capable of generating stable soliton mode-locked pulses with a pulse duration of 1.58 ps at a center wavelength of 1951 nm with a signal to noise ratio (SNR) of more than 60 dB, as well as a peak power of 250 mW and a pulse energy of 0.39 nJ.